Municipal waste components and their collection by computer support - Volek, Josef (Univerzita Pardubice, 2010)
Growing volumes of different waste types produced by industrial companies represent a serious threat for the environment. Unthoughtful waste liquidation by means of dumping results to massive valuable resources wasting on one hand and in environment pollution by greenhouse gases emissions into the air, endangering underground water by extract liquid seepage and soil contamination by heavy metals on the other. The only possible method of a sustainable development is a consistent separation of reusable materials contained in waste and their consequent recycling, separation of combustible waste by means of environment-friendly technologies, by separation of bio-degradable materials suitable for composting with a consequent return into natural nutriment cycle, and last but not least, by separation of hazardous waste components and their ecological /liquidation/use. The article focuses on the options of operational research methods in combustible waste management, handling separated bio-degradable municipal waste components and hazardous waste management in the Pardubice Region. This research is funded by the Research Project Theory of Transportation Systems MSM 0021627505.
Keywords: municipal waste; combustible waste; bio-degradable waste; hazardous waste; computer-aided decision making; operational research; theory of graphs; location analysis